A dual-output switched-capacitor regulator with a self-controlled ripple reduction technique for self-powered EEG acquisition. (May 2023) - Vafaei, Mehrnoosh; Rahiminejad, Zahra; Abiri, Ebrahim; Salehi, Mohammad Reza
Abstract: In this paper, a novel dual-output switched-capacitor (SC) regulator is designed for EEG acquisition. At first, an efficient reconfigurable SC is designed with conversion ratios of 2/3 and 1/4 from 1.3 V input voltage. Reconfigurable SC with pulse frequency modulation (PFM) technique produces two single output voltages of 0.8 V and 0.2 V by changing the digital bit S . Then, a novel algorithm is proposed to produce two output voltages simultaneously and reduce voltage ripple. This SC regulator is self-controlled, and its control digital bits are entirely generated by the control logic circuit. Load current range is proportional to the EEG acquisition, in the range of 5 nA-1 μA and 500 nA-260 μA, for output voltages of 0.2 V and 0.8 V, respectively. The proposed dual-output SC is simulated in TSMC 65 nm CMOS technology and occupies an area of 2.09 mm 2 . The proposed SC regulator achieves a maximum power efficiency and output power of 92.8% and 193 μW, respectively.